Skeletal muscle antagonizes antiviral CD8+ T cell exhaustion - Wu, Jingxia; Hotz-Wagenblatt, Agnes; Hering, Marvin; Cui, Guoliang (Science advances, 2020)
CD8(+) T cells become functionally impaired or "exhausted" in chronic infections, accompanied by unwanted body weight reduction and muscle mass loss. Whether muscle regulates T cell exhaustion remains incompletely understood. We report that mouse skeletal muscle increased interleukin (IL)-15 production during LCMV clone 13 chronic infection. Muscle-specific ablation of //15 enhanced the CD8(+) T cell exhaustion phenotype. Muscle-derived IL-15 was required to maintain a population of CD8(+)CD103(+) muscle-infiltrating lymphocytes (MILs). MILs resided in a less inflamed microenvironment, expressed more T cell factor 1 (Tcf1), and had higher proliferative potential than splenic T cells. MILs differentiated into functional effector T cells after reentering lymphoid tissues. Increasing muscle mass via muscle-specific inhibition of TGF beta signaling enhanced IL-15 production and antiviral CD8(+) T cell responses. We conclude that skeletal muscle antagonizes T cell exhaustion by protecting T cell proliferative potential from inflammation and replenishing the effector T cell progeny pool in lymphoid organs.
Im Titel ist das Zeichen + hochgestellt
Gesehen am 13.08.2020